2022
DOI: 10.1186/s12891-022-05244-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arthroscopy versus percutaneous radiofrequency thermal ablation for the management of intra- and juxta-articular elbow osteoid osteoma: case series and a literature review

Abstract: Background Today, intra-articular and juxta-articular osteoid osteomas are treated with arthroscopy and radiofrequency thermal ablation. However, for the case of an elbow joint, arguments are made for the use of a minimally invasive technique to be the optimal choice. This study aims to analyse our experiences of arthroscopically treated elbow osteoid osteomas and to compare it with the published results of both techniques. Methods The retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…One year after surgery, all pain symptoms completely disappeared, and the right elbow range of motion increased to 30° to 145°. Knezevic et al [ 23 ] conducted a case-control analysis of patients with elbow joint OO, treated with arthroscopic radiofrequency ablation and percutaneous radiofrequency ablation under CT guidance by the same surgeon at the same institution over approximately 6 years. They stated that arthroscopy can precisely locate the lesion before radiofrequency ablation, collect samples for pathological biopsy, further confirm the tumor diagnosis, and minimize damage to the cartilage and surrounding soft tissues during the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One year after surgery, all pain symptoms completely disappeared, and the right elbow range of motion increased to 30° to 145°. Knezevic et al [ 23 ] conducted a case-control analysis of patients with elbow joint OO, treated with arthroscopic radiofrequency ablation and percutaneous radiofrequency ablation under CT guidance by the same surgeon at the same institution over approximately 6 years. They stated that arthroscopy can precisely locate the lesion before radiofrequency ablation, collect samples for pathological biopsy, further confirm the tumor diagnosis, and minimize damage to the cartilage and surrounding soft tissues during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This has been widely promoted in the field of orthopedics. [23,24] Alrassasi et al [25] conducted a case analysis of a 28-yearold female patient with OO of the right elbow. The patient had contracture of the right elbow, with a range of motion between 50° and 110°.…”
Section: Treatment 621 Limitations and Challenges Of Traditional Trea...mentioning
confidence: 99%
“…What is more, arthroscopy allows the handling of many other conditions simultaneously. Studies have demonstrated successful applications of arthroscopy in osteoid osteoma 28–31 . Interestingly, for intra‐ and juxta‐articular localization of osteoid osteoma, arthroscopy‐assisted radiofrequency ablation was proposed 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated successful applications of arthroscopy in osteoid osteoma. 28 , 29 , 30 , 31 Interestingly, for intra‐ and juxta‐articular localization of osteoid osteoma, arthroscopy‐assisted radiofrequency ablation was proposed. 31 , 32 , 33 This technique synthesizes both of the strengths.…”
Section: Discussionmentioning
confidence: 99%
“…21 Knežević et al published their series (6 patients) and a review of the literature (23 patients) on OO involving the elbow with success rates of 86.4%-96.3%, minimal complication rates, and recurrence rates of 0%-3.7%. 30 Ge et al also published a review of 19 patients with OO of the elbow who underwent arthroscopic treatment. They reported good functional outcomes with 10.5% reoperations and 10.5% complications.…”
Section: Discussionmentioning
confidence: 99%